Pengaruh Motivasi terhadap Kinerja Pegawai Dinas Pendidikan Provinsi Sulawesi Barat: Analisis Teori Motivasi Intrinsik Herzberg: The Influence of Motivation on the Employees’ Performance of the West Sulawesi Provincial Education Office: Analysis of Herzberg’s Intrinsic Motivation Theory - Jawahira Jawahira; Muh Ikhtiar; Haeruddin Haeruddin (Al-Musannif, 2024)
The purpose of this study was to analyze the effect of work motivation on the performance of employees of the West Sulawesi Provincial Education Office. Motivation in this study is based on four indicators of Herzberg's intrinsic motivation: responsibility, work performance, job satisfaction, and opportunities for advancement. The type of research used is analytical observational research using cross-sectional studies. The number of population was 163; the sampling technique was total sampling. The data analysis techniques used were univariate analysis, bivariate analysis (chi-square), and multivariate analysis with logistic regression. The results show that responsibility, work performance, and opportunities for advancement significantly influence employee performance, while job satisfaction does not significantly influence employee performance. This study has implications for the importance of job promotions to be based on performance, not political promotions. This can make employees have positive and emotional feelings about their work.